Full Life Cycle Management of Power System Integrated With Renewable Energy: Concepts, Developments and Perspectives - Wang, Kang; Li, Yikai; Wang, Xiaojun; Zhao, Zengtao; Yang, Ning; Yu, Shengcan; Wang, Yi; Huang, Zhanhong; Yu, Tao (Frontiers in Energy Research, 2021)
Under high-penetration of renewable energy, power grid is facing with the development problems such as production delay, wind and solar power abandoning. With the continuous growth of renewable energy installation such as wind power, photovoltaic (PV), as well as the increase of power generation capacity, it is urgent to increase peak-load and frequency regulation capacity on a large scale to alleviate the consumption problems caused by large renewable energy integration, and then requires power generation enterprises of peak-load and frequency regulation to increase relevant equipment assets. As a result, peak-load and frequency regulation enterprises must carry out scientific cost management of equipment assets. This paper introduces the concepts, developments and perspectives of life cycle cost (LCC) management of equipment assets in high-penetrated renewable energy power grid, and probes into cost collection and estimation scheme in the process of equipment asset management.